Actual issues of organ donation. Introduction. The lecture. - V. L. V.L. Vinogradov (Трансплантология (Москва), 2016)
Further development of transplantation is becoming increasingly problematic despite the impressive achievements. A deficit of donor organs is becoming the main constraint factor of its development in the world and in Russia. This article is an introduction to a series of review articles on actual issues of organ donation.